2015
DOI: 10.3389/fncel.2015.00127
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in focal ictal activity following transplantation of MGE interneurons requires expression of the GABAA receptor α4 subunit

Abstract: Despite numerous advances, treatment-resistant seizures remain an important problem. Loss of neuronal inhibition is present in a variety of epilepsy models and is suggested as a mechanism for increased excitability, leading to the proposal that grafting inhibitory interneurons into seizure foci might relieve refractory seizures. Indeed, transplanted medial ganglionic eminence interneuron progenitors (MGE-IPs) mature into GABAergic interneurons that increase GABA release onto cortical pyramidal neurons, and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…Some evidence suggests that MGE transplants also reduce mossy fiber sprouting (Henderson et al, 2014; but see Hunt et al, 2013). After transplantation into the hippocampus of mice with TLE, fetal mouse MGE progenitors were linked to increased spontaneous IPSCs in hippocampal GCs (Henderson et al, 2014) and increased phasic and tonic inhibition in other populations of host brain neurons (Baraban et al, 2009; Hsieh and Baraban, 2017) via α4 subunit containing GABA A receptors (Jaiswal et al, 2015). The notion that transplanted neurons integrate into host brain circuits and provide synaptic inhibition is further supported by optogenetic experiments showing that stimulation of transplanted channelrhodopsin 2 (ChR2)-expressing GABAergic neurons induced strong IPSCs in hippocampal neurons (Henderson et al, 2014; Hsieh and Baraban, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that MGE transplants also reduce mossy fiber sprouting (Henderson et al, 2014; but see Hunt et al, 2013). After transplantation into the hippocampus of mice with TLE, fetal mouse MGE progenitors were linked to increased spontaneous IPSCs in hippocampal GCs (Henderson et al, 2014) and increased phasic and tonic inhibition in other populations of host brain neurons (Baraban et al, 2009; Hsieh and Baraban, 2017) via α4 subunit containing GABA A receptors (Jaiswal et al, 2015). The notion that transplanted neurons integrate into host brain circuits and provide synaptic inhibition is further supported by optogenetic experiments showing that stimulation of transplanted channelrhodopsin 2 (ChR2)-expressing GABAergic neurons induced strong IPSCs in hippocampal neurons (Henderson et al, 2014; Hsieh and Baraban, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MGE grafts enhance both synaptic and extrasynaptic inhibition (Baraban et al, 2009). Interestingly, the requirement of extrasynaptic GABA-A receptors for the transplant-mediated dampening of seizure propagation in the 4-AP model was recently shown (Jaiswal et al, 2015). Given the heterogeneity of MGE transplant-derived interneurons, it will be important to identify whether specific subtypes may prove therapeutic for specific forms of seizures.…”
Section: Disease-modifying Properties Of Mge Transplantsmentioning
confidence: 93%
“… 9 It is suggested that there is a connection between the pyramidal neurons and the newly formed interneurons which produces the inhibitory effect. 87 Further investigation in clinical GABAergic cell therapy must explore the long-term effects of grafting, results in drug-resistant epilepsy, and usefulness in reducing the cognitive and mood impairments associated with epilepsy. 9 …”
Section: Stem Cell Therapy and Epilepsymentioning
confidence: 99%